Role of nuclear factor kappa B and reactive oxygen species in the tumor necrosis factor-a-induced epithelial-mesenchymal transition of MCF-7 cells - Dong,R. (2007)
The microenvironment of the tumor plays an important role in facilitating cancer progression and activating dormant cancer cells. Most tumors are infiltrated with inflammatory cells which secrete cytokines such as tumor necrosis factor-a (TNF-a). To evaluate the role of TNF-a in the development of cancer we studied its effects on cell migration with a migration assay. The migrating cell number in TNF-a -treated group is about 2-fold of that of the control group. Accordingly, the expression of E-cadherin was decreased and the expression of vimentin was increased upon TNF-a treatment. These results showed that TNF-a can promote epithelial-mesenchymal transition (EMT) of MCF-7 cells. Further, we found that the expression of Snail, an important transcription factor in EMT, was increased in this process, which is inhibited by the nuclear factor kappa B (NFkB) inhibitor aspirin while not affected by the reactive oxygen species (ROS) scavenger N-acetyl cysteine. Consistently, specific inhibition of NFkB by the mutant IkBa also blocked the TNF-a-induced upregulation of Snail promoter activity. Thus, the activation of NFkB, which causes an increase in the expression of the transcription factor Snail is essential in the TNF-a-induced EMT. ROS caused by TNF-a seemed to play a minor role in the TNF-a-induced EMT of MCF-7 cells, though ROS per se can promote EMT. These findings suggest that different mechanisms might be responsible for TNF-a - and ROS-induced EMT, indicating the need for different strategies for the prevention of tumor metastasis induced by different stimuli.